Transcriptomic analyses of the anti-adipogenic effects of oleuropein in human mesenchymal stem cells. Issue 3 (28th February 2017) - Casado-Díaz, Antonio; Anter, Jaouad; Müller, Sören; Winter, Peter; Quesada-Gómez, José Manuel; Dorado, Gabriel
Abstract : Transcriptomic analysis in human MSC differentiated into adipocytes in presence of oleuropein, identifies possible pathways responsible for its antiadipogenic effect. Abstract : Extra virgin olive oil has positive effects on health. Oleuropein is a polyphenolic compound present in olive-tree leaves, fruits (olives) and olive oil. It is responsible for the relevant organoleptic and biological properties of olive oil, including antiadipogenic properties. Thus, the effects of oleuropein on the adipogenesis of human bone-marrow mesenchymal stem cells were studied by transcriptomics and differential gene-expression analyses. Oleuropein could upregulate expression of 60% of adipogenesis-repressed genes. Besides, it could activate signaling pathways such as Rho and β-catenin, maintaining cells at an undifferentiated stage. Our data suggest that mitochondrial activity is reduced by oleuropein, mostly during adipogenic differentiation. These results shed light on oleuropein activity on cells, with potential application as a "nutraceutical" for the prevention and treatment of diseases such as obesity and osteoporosis.